Modular independent sewerage treatment system design for domestic residence at water villagers in Sabah, Malaysia - Mazandarani, Navid Nasrolah (2016)
There is a need to maintain water quality by improving the quality of domestic sewage discharge for reducing coastal contamination at remote water village settlements. The purpose of this study is to develop smallest modular design for an independent sewerage treatment plant (iSTP) system for reducing water contamination at timber water villages. This study focused on conducting quality discharge tests on sewage inflows covering BOD5, COD, TSS, pH and AN. In addition, it is hypothesized that by controlling 5 person sewage inflows for a timber house, the size of the STP could be reduced by adding oxygen transfer efficiency (OTE) technology with controlled aeration time to maintain quality discharge compatible with Malaysian water standards. This study started with test results of an iSTP 600 L system design and its overall Standard A average according to SPAN (2009). The results help determined the specifications for designing one iSTP 350 L system. The next step was conducting the design calculation for structural loading to timber structures for supporting the iSTP 350 L system design. The results of the study include the development of a proof-ofconcept prototype for determining and recommending the design specifications of the smallest iSTP system for timber structures. In essence, the study proposed a 350 L iSTP system prototype which is capable of discharging good water quality. The quality of the new iSTP system prototype was checked against 5 environmental tests (i.e., BOD5, COD, TSS, AN, pH) and meets the Standard A requirements according to SPAN (2009) with 6 hours aeration time. The 350 L iSTP system is a modular system that enables suspended installation under the structural framing system of a raised floor which allows easy transportation, installation and maintenance in environmentally sensitive locations. The iSTP 350 L system design is unique due to its modular and detachable components with possibilities to be installed on columns and beams. Future studies are recommended to add oil and grease test, use of advanced media and improve the horizontal attachment system of the chambers.